Implementasi Fair Trade dalam Perdagangan Komoditas Kacang Mete dari Bali Timur - Putu Ratih Kumala Dewi; Adi P. Suwecawangsa (Pusat Kajian Bali Universitas Udayana, 2022)
Due to the COVID-19 pandemic fair trade is thought to be a trading plan that can aid economic recovery. Companies that conduct fair trade schemes, on the other hand, face hurdles as a result of the economic crisis brought on by the pandemic. The East Bali Cashews (EBC) company, which offers fair trade for cashew nuts as a major commodity in Ban village, Karangasem, is highlighted in this study. This study seeks to explain the role of corporation as non-state actor in international trade by adopting a pluralist approach and the concept of fair trade. The study compares the implementation of fair trade by EBC during the COVID-19 pandemic with before the pandemic using a comparative qualitative method with primary data obtained through in-depth interviews. This study is significant in examining the critical role of corporation as primary actor in fair trade schemes that directly affect cashew farmers as small producers. In order to advance the welfare of farmers and cashew as a promising commodity for Ban Village's development.